2018
DOI: 10.2741/4684
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 and gama-Semino protein as possible prognostic marker of prostate cancer

Abstract: In the United States, Prostate Cancer (PCa) is the leading cause of cancer-related mortality in men. PCa resulted in abnormal growth and function of prostate gland such as secretion of high level of gamma-seminoprotein (gama-SM)/Prostate-Specific Antigen (PSA) which could be detected in the blood. Beside gama-SM protein, the levels of heat shock proteins (Hsp70) were also observed significantly high. Therefore, gama-SM and Hsp70 are unique proteins with high potential for PCa therapeutics and diagnostics. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
2
5
0
Order By: Relevance
“…The surrounding normal brain tissue in grade 4 GBM showed a very low Hsp70 staining intensity. In line with previous data [18], grade 3 gliomas show predominantly a nuclear staining pattern, whereas grade 4 GBM shows a positive staining in both the nucleus and cytosol.…”
Section: Comparison Of Intracellular and Circulating Hsp70 Levels In ...supporting
confidence: 92%
See 2 more Smart Citations
“…The surrounding normal brain tissue in grade 4 GBM showed a very low Hsp70 staining intensity. In line with previous data [18], grade 3 gliomas show predominantly a nuclear staining pattern, whereas grade 4 GBM shows a positive staining in both the nucleus and cytosol.…”
Section: Comparison Of Intracellular and Circulating Hsp70 Levels In ...supporting
confidence: 92%
“…Formalin-fixed paraffin-embedded (FFPE) sections (3 µm) of grade 3 and grade 4 brain tumors were stained with the cmHsp70.1 mAb, as described previously [18]. Briefly, after dewaxing and rehydrating in xylol (Karl Roth GmbH, Karlsruhe, Germany) and descending concentrations of ethanol (96% v/v Otto Fischar GmbH, Saarbrücken, Germany), sections were heated at 60 • C for 30 min for antigen retrieval.…”
Section: Measurement Of Intracellular Hsp70 By Immunohistochemistry O...mentioning
confidence: 99%
See 1 more Smart Citation
“…HSP70, a member of the evolutionarily highly conserved heat shock protein family, plays an important role in enhancing cell resistance to various stimuli and alleviating cell damage via its molecular chaperone function in protein folding, unfolding, and disaggregation (26). Lines of studies have revealed that the basal level of HSP70 was high in several types of malignancies (27)(28)(29)(30)(31) and that it has been categorized as a bad prognosis factor (27,28). HSP70 has also been demonstrated to cooperate in chemotherapy and radiotherapy resistance probably due to its capacity to disable cell death (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…This may not only be due to decreased pro-apoptotic activity resulting from lower Axud1 levels in mammals, but also to increased hsp70 expression at levels that foster cell survival. Likewise, this relation (lower Axud1 expression and higher Hsp70 levels) has been independently documented in multiple studies, being related to progression and poor prognosis for prostate cancer [ 49 , 50 ], lung squamous cell carcinoma [ 19 , 51 ], and hepatocellular carcinoma [ 14 , 52 ]. In any case, this relationship between low levels of Axud1 and high levels of Hsp70 in the progression and aggressiveness of cancers must be confirmed in studies conducted for this purpose.…”
Section: Discussionmentioning
confidence: 93%